Racial/ethnic differences in adolescents’ non-response to suicide attempt: Findings from the Youth Risk Behavior Survey, 2015–2019 - Baiden, P.; Baiden, P.; Mets, V.E.; et al. (Journal of Psychiatric Research, 2023)
Racial/ethnic minority adolescents are at greater risk of attempting suicide compared to their White counter parts. Yet, racial/ethnic minority adolescents are more likely to not respond to questions on suicidal behaviors. The objective of this study was to investigate the association between race/ethnicity and missing response to suicide attempt among adolescents in the United States. Data for this study were obtained the 2015–2019 na tional Youth Risk Behavior Survey (n = 40,360). The outcome variable investigated in this study was missing response to suicide attempt and the main explanatory variable was race/ethnicity. Two hierarchical binary lo gistic regression models were fitted to examine the association between race/ethnicity and missing response to suicide attempt. Of the 40,036 adolescents, 13.4% had missing response to suicide attempt. Controlling for the effects of demographic factors and symptoms of depression, adolescents who self-identified as non-Hispanic Black had more than threefold higher odds of having missing response to suicide attempt when compared to their non-Hispanic White counterparts (AOR = 3.62, p < .001, 95% CI = 2.45–5.34). Adolescent males and adolescents questioning their sexual identity had higher odds of having missing response to suicide attempt. Adolescents with depressive symptoms had lower odds of having missing response to suicide attempt. Missing response to suicide attempt among adolescents continues to differ by race/ethnicity and other demographic factors. The use of a single item in assessing suicide attempt history may be inadequate in capturing national estimates of adolescent suicide metrics.
Research Artilce
Keywords: Missing response; Suicide attempt; Race/ethnicit